2020
DOI: 10.1186/s12931-020-01517-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of diurnal temperature range with daily hospitalization for exacerbation of chronic respiratory diseases in 21 cities, China

Abstract: Background The association between diurnal temperature range (DTR) and hospitalization for exacerbation of chronic respiratory diseases (CRD) was rarely reported. Objectives To examine the association between DTR and daily hospital admissions for exacerbation of CRD and find out the potential effect of modifications on this association. Method Data on daily hospitalization for exacerbation of chronic obstructive pulmonary disease (COPD), asthma and bronchiectasis and meteorology measures from 2013 through … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…In this study, the exposure-response curves between DTR and the daily outpatient visits of URTI in all, male and female college students were close to linear upward trends at lag 0-6 days. These linear-like trends were also found in previous studies (Wang et al 2020;Zheng et al 2016). Therefore, the generalized additive models were used by us to investigate the associations of DTR and the outpatient visits for URTI.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, the exposure-response curves between DTR and the daily outpatient visits of URTI in all, male and female college students were close to linear upward trends at lag 0-6 days. These linear-like trends were also found in previous studies (Wang et al 2020;Zheng et al 2016). Therefore, the generalized additive models were used by us to investigate the associations of DTR and the outpatient visits for URTI.…”
Section: Discussionsupporting
confidence: 90%
“…However, in some other studies, U-or J-shaped exposure-response curves between DTR and the occurrence of adverse outcomes were revealed (Deng et al 2020;Hu et al 2018;Zhao et al 2017). A study conducted in Hefei even showed slightly M-shaped exposure-response curve between DTR and the risk of admissions for tuberculosis (Huang et al 2020). The reasons for such inconsistent results might be that the types of population and disease in these studies were very different.…”
Section: Discussionmentioning
confidence: 95%
“…Many previous studies pointed out that DTR was still associated with mortalities and emergency room admissions for a variety of cardiovascular and respiratory diseases when adding air pollutants to model ( In this study, the exposure-response curves between DTR and the daily outpatient visits of URTI in all, male and female college students were close to linear upward trends at lag 0-6 days. These linear-like trends were also found in previous studies (Wang et al 2020;Zheng et al 2016). Therefore, the generalized additive models were used by us to investigate the associations of DTR and the outpatient visits for URTI.…”
Section: Discussionsupporting
confidence: 71%
“…Deng et al 2020;Hu et al 2018;Zhao et al 2017). A study conducted in Hefei even showed slightly M-shaped exposure-response curve between DTR and the risk of admissions for tuberculosis(Huang et al 2020). The reasons for such inconsistent results might be that the types of population and disease in these studies were very different.The strongest effect values of DTR were found at the current day in the models of single-day lags, whether for male, female, or all college students.…”
mentioning
confidence: 99%
“…More trauma patients, a higher proportion of young patients [ 20 ], and more orthopedic trauma consultation [ 10 ] occurred in summer than in winter in the US and the UK. Wider diurnal temperature ranges in cold seasons were associated with more patients with chronic respiratory diseases, but less in hot seasons [ 21 ]. Most interestingly exposure to heat in warm seasons had no impact on hospital admissions for cardiovascular and respiratory reasons in Spanish cities but was associated with higher mortality risks.…”
Section: Introductionmentioning
confidence: 99%